Opposing Roles of Nucleus Accumbens Core and Shell Dopamine in the Modulation of Limbic Information Processing - Ito, Rutsuko (Society for Neuroscience, 2011)
The dopaminergic innervation of the nucleus accumbens (NAc) is implicated in the selection and integration of motivationally relevant corticolimbic information that governs behavioral output. However, it is unknown whether the dopaminergic innervations of two anatomically distinct subregions of the NAc, core and shell, have differential roles in this gating process, and whether dopaminergic mechanisms are important in regulating the balance of limbic control over appetitive behavior at the point of learning. Having previously shown that repeated systemic pretreatment with amphetamine disrupts the regulation of competing limbic control over appetitive behavior in mice, we hereby examined the effects of repeated pretraining intra-NAc shell or core microinfusions of d-amphetamine, general dopamine (DA) receptor antagonist cis-flupenthixol, or vehicle solution (saline) upon a simultaneously acquired conditioned cue and place preference task in rats. Repeated infusions of amphetamine into the NAc shell and core had opposite effects on the acquisition of conditioned place preference by significantly enhancing and attenuating, respectively, hippocampal-dependent place conditioning. In contrast, direct infusions of flupenthixol into the NAc shell attenuated place conditioning, while NAc core flupenthixol infusions not only attenuated cue conditioning, but also enhanced conditioned place preference. These findings implicate the NAc shell DA as being necessary for enabling hippocampal-dependent spatial information to gain control over appetitive learning, and the NAc core DA as being important for allowing basolateral amygdala-dependent information to gain control over appetitive learning. It is further proposed that NAc core DA may be critical in regulating limbic information flow through the NAc shell.